State of Human Security in Security State: A Case Study of Pakistan - Shahnawaz, Shahnawaz (GMPI Conference Series, 2022)
Human Security is one of the novel concepts in international relations developed by the United Nations Development Projects (UNDP). The concept of human security revolves around protecting people from illiteracy, diseases, non-development, and food security. It describes how the state is developing and investing in human development and human capabilities. It is significant to note that international relations literature critically focuses on national security and the importance of state security. Most pundits of international relations do not give importance to human security and assert that the state should protect and invest in its national security instead of human security. However, some countries are utterly focused on national security and spend a significant amount on that, like Pakistan, which spends around 1.37 trillion Pakistani rupees (USD 8.78 billion) for 2021. According to the Asian Development Bank 24% of the population is living below the poverty line. This study is qualitative research that mainly employs case study methodology. Therefore, this paper analyzes whether illiteracy and poverty are a threat to the country's national security. How can national security be improved by investing in human security? This research analysis discovers that human security is equally essential for any state that profoundly focuses on national security and sovereignty by investing more in defense acquisition and military needs. In addition, the study concludes that lack of investment in human security is triggering extreme poverty, illiteracy, and religious radicalization, causing a direct threat to Pakistan's national security.